A biorelevant test for tablets glycine sublingual in the «simulated saliva» dissolution medium - S. D. Kulikova; М. B. Sokol; Z. M. Kozlova; P. A. Losenkova; P. Ya. Parshinova; A. M. Poluyanov (Разработка и регистрация лекарственных средств)
Introduction. Biorelevant dissolution media reconstitute the composition of the contents of the gastrointestinal tract. They are used as dissolution media in the evaluation of dissolution profiles of different dosage forms. Simulated biological fluids allow prediction of in vivo test results. The development of the composition of simulated salivary fluid allows the evaluation of drug properties under physiologically relevant conditions.Aim. Evaluation of the release of the drug product "glycine, sublingual tablets, 100 mg", domestically produced in Simulated Saliva 5 pH 6.8.Materials and methods. The preparations used for analysis were: «Glycine, sublingual tablets, 100 mg», domestically produced with valid expiration date. Comparative dissolution kinetics test was carried out on the dissolution test apparatus DT 6 (ERWEKA GmbH, Germany). Chromatographic separation and detection were performed on a Waters W1525 Binary HPLC Pump high-performance liquid chromatograph (Waters Corporation, USA) equipped with column and sample thermostat, degasser, autosampler and Waters 2487 Dual Absorbance Detector (Waters Corporation, USA). Detection was performed at a wavelength of 254 ± 2 nm after derivatization of the glycine molecule with 4-toluenesulfonyl chloride. A Grace Platinum C18-EPS 5 μm 4.6 × 250 mm Grace Platinum C18-EPS 5 μm 4.6 × 250 mm column (Grace, USA) and a Grace Platinum C18-EPS 5 μm 4.6 × 250 mm pre-column (Grace, USA) were used. The following software was used for the study: validated Microsoft Excel spreadsheet for calculating glycine release values.Results and discussion. The technique for quantitative determination of glycine was developed and validated under CDKT in purified water medium and Simulated Saliva 5 pH 6.8. The validated analytical range of the methodology was 10–110 % of the nominal concentration of the dosage form in 300 mL volume of medium. The developed analytical technique was validated in the biopredictive in vitro test of glycine preparations. During the study in Simulated Saliva medium for drug formulations, more discriminative data were obtained, which were expressed as: different dissolution rate, curvature of the slope of the dissolution profile and time to reach the plateau in contrast to the dissolution medium purified water.Conclusion. The quantification technique was developed and validated for biopredictive tests of tablets "Glycine, sublingual tablets, 100 mg". The analytical range of the technique was 10–110 % of the nominal concentration of the dosage form in 300 mL volume of medium. The results of the test in artificial saliva medium were more discriminatory.